2017
DOI: 10.4103/0974-8490.199771
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition and morphological alteration of Fusarium sporotrichioides by Mentha piperita essential oil

Abstract: Objective:The aim of this study is to determine the phytochemical composition, antifungal activity of Mentha piperita essential oil (MPE) against Fusarium sporotrichioides.Methods:The phytochemical composition was conducted by gas chromatography mass spectrometry (GC MS) analysis and mycelia growth inhibition was determined by minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC), the morphological characterization was observed by scanning electron microscopy. Finally, the membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 48 publications
(50 reference statements)
3
9
0
Order By: Relevance
“…Hammer et al [33] reported significant incremental increases (p < 0.05) in the absorbance of the supernatants of the C. albicans and C. glabrata treated with tea tree EO (0.25% to 1.0%) after the 6 h. Furthermore, an increase in the absorbance was observed from the supernatant of D. hansenii at 128 and 256 μg/mL of carvacrol or thymol after 6 h [19]. Similar results have been reported for eugenol (50 to 200 μg/mL) against B. cinerea [20]; eugenol (32 μg/mL), or geraniol (32 and 64 μg/mL), against T. rubrum [13,14]; cinnamon EO (0.05 or 0.1 μL/mL) against R. nigricans [36]; M. piperita EO (500 or 1000 μL/mL) against F. sporotrichioides [34]; cinnamaldehyde (128 μg/mL) and eugenol (256 μg/mL) against C. glabrata [39]; and trans-cinnamaldehyde (0.313 µg/mL) against Penicillium italicum [22]. Rajkowska et al [40] conducted this test and expressed the results for DNA concentration (μg/mL) using the formula:…”
Section: Cellular Leakage Assay (Leakage Of Cytoplasmic Content)supporting
confidence: 81%
See 3 more Smart Citations
“…Hammer et al [33] reported significant incremental increases (p < 0.05) in the absorbance of the supernatants of the C. albicans and C. glabrata treated with tea tree EO (0.25% to 1.0%) after the 6 h. Furthermore, an increase in the absorbance was observed from the supernatant of D. hansenii at 128 and 256 μg/mL of carvacrol or thymol after 6 h [19]. Similar results have been reported for eugenol (50 to 200 μg/mL) against B. cinerea [20]; eugenol (32 μg/mL), or geraniol (32 and 64 μg/mL), against T. rubrum [13,14]; cinnamon EO (0.05 or 0.1 μL/mL) against R. nigricans [36]; M. piperita EO (500 or 1000 μL/mL) against F. sporotrichioides [34]; cinnamaldehyde (128 μg/mL) and eugenol (256 μg/mL) against C. glabrata [39]; and trans-cinnamaldehyde (0.313 µg/mL) against Penicillium italicum [22]. Rajkowska et al [40] conducted this test and expressed the results for DNA concentration (μg/mL) using the formula:…”
Section: Cellular Leakage Assay (Leakage Of Cytoplasmic Content)supporting
confidence: 81%
“…Permeability of the cell membrane can be expressed in terms of electrical conductivity and extracellular pH values. Rachitha et al [34] measured the extracellular pH of Fusarium sporotrichioides following Mentha piperita EO treatment. The fungal cell suspension (10 5 spores/mL) was added to 20 mL of the liquid medium and then incubated at 28 °C for 20 min.…”
Section: Extracellular Ph and Conductivity Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, fungicide-resistant fungal races have emerged due to the indiscriminate use of synthetic fungicides (VERWEIJ et al, 2009;ARENDRUP et al, 2010;TATEISHI et al, 2014). Therefore, several plant species have been studied, and the essential oil of many of them have presented antifungal activity, such as Corymbia citriodora, Cymbopogon nardus (AGUIAR et al, 2014), Myrcia ovata (SAMPAIO et al, 2016), Myrcia lundiana (ALVES et al, 2016;ALVES et al, 2018), Lippia alba (PEIXOTO et al, 2018), Curcuma longa (HU et al, 2017), and Mentha piperita (RACHITHA et al, 2017). These metabolites are considered as a safer alternative for the control of these pathogens since they are biodegradable and have low toxicity and low risk of developing resistance in microorganisms (RUSSO et al, 2013).…”
Section: Introductionmentioning
confidence: 99%